Analysis of the Success of Implementing the Village Financial System on Village Governance: Empirical Study in Tulungagung Regency, East Java, Indonesia - Sindi Yulika Putri; Loggar Bhilawa (International Journal of Social, Economic, and Business, 2024)
This research aims to find empirical evidence regarding the successful implementation of the Village Financial System (SISKEUDES) and its influence on village governance in Tulungagung Regency. This study employs a quantitative approach and evaluates a model based on the DeLone & McLean IS Success Model as well as the theory of trust and legitimacy. This success model includes variables such as information quality (IQ), system quality (SQ), service quality (SEQ), trust in technology (TIT), user satisfaction (US), operational effectiveness (OE), and village governance (VG). Data collection was carried out using a cluster sampling technique, obtaining 82 sample villages that use SISKEUDES. The analysis technique used in this research is SEM-PLS using SmartPLS. The research results show that IQ, SQ, and TIT have a positive effect on US, while SEQ has no effect on US. TIT and US have a positive effect on OE, while IQ, SQ. and SEQ have no effect on OE. OE is proven to have a positive effect on VG. The results of this research show that the implementation of SISKEUDES in Tulungagung Regency has been successful, and the implementation of SISKEUDES can improve village governance, especially accountability, transparency, and participation.